Analytical characterization of gaseous slip flow and heat transport through a parallel-plate microchannel with a centered porous substrate. Issue 3 (3rd May 2016) - Wang, Keyong; Vafai, Kambiz; Wang, Dazhong
Abstract : Purpose: – The purpose of this paper is to analytically perform gaseous slip flow and heat transfer analysis within a parallel-plate microchannel partially filled with a centered porous medium under local thermal non-equilibrium (LTNE) condition. Heat transfer of gaseous flow in a porous microchannel is analytically studied. Energy communication at the porous-fluid interface is considered by two approaches: the gas rarefaction negatively impacts the heat transfer performance, and the optimum ratio of porous thickness is found to be around 0.8. Design/methodology/approach: – Both Models A and B are utilized to consider the heat flux splitting for the fluid and solid phases at the porous-fluid interface. Findings: – Analytical solutions for the fluid and solid phase temperature distributions and the Nusselt number are derived. In the no-slip flow limit, the present analytical solutions are validated by the partially and fully filled cases available in the literature. Research limitations/implications: – The continuum flow (no-slip flow) is only a special case of the slip flow. Meanwhile, the effects of pertinent parameters on the heat transfer are also discussed. Practical implications: – A survey of available literature mentioned above indicates a shortage of information for slip flow and heat transfer in partially filled porous systems. The main objective of the present study is to investigate the slip flow and heat transfer characteristics for forced convection through a microchannel partially filled with a porous medium under LTNE condition. The porous substrate is placed at the center of the microchannel. Analytical solutions for the temperature distributions of the fluid and solid phases and the Nusselt number at the microchannel wall are obtained. Originality/value: – Heat transfer of gaseous flow in a porous microchannel is analytically studied. Energy communication at the porous-fluid interface is considered by two approaches: the gas rarefaction negatively impacts the heat transfer performance, and the optimum ratio of porous thickness is found to be around 0.8. Gaseous slip flow and heat transfer analysis is analytically performed within a parallel-plate microchannel partially filled with a centered porous medium under LTNE condition. Analytical solutions for the fluid and solid phase temperature distributions and the Nusselt number are derived for the first time. The effects of pertinent parameters on the heat transfer are also discussed. Compared with the results obtained for the continuum flow regime, the gas rarefaction negatively impacts the heat transfer efficiency and has little influence on the optimal porous thickness.